Open-label, randomized, crossover comparative bioavailability study of cefixime from two tablet formulations after single oral administration - Patil, Saiprasad; Hajare, Anoop L.; Krishnaprasad, K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cefixime is an oral extended spectrum third generation cephalosporin, which has marked in vitro bactericidal activity against a wide variety of Gram-positive and Gram-negative organisms, effective in the treatment of community-acquired infections such as respiratory tract infection and urinary tract infection. The objective of this randomized, crossover study was to compare the bioequivalence (BE) of two tablets of test (Milixim® 200 mg, containing 200 mg of cefixime) with Reference formulation (Cefixime, 400 mg). Methods: A total of 12 healthy volunteers were randomly assigned to crossover, single-dose treatment regimens. Serial blood samples were collected, and plasma concentrations of cefixime were analyzed using the high-performance liquid chromatographic technique. Pharmacokinetic parameters and BE limits were calculated using non-compartmental methods. Results: The mean Cmax for the test and reference formulations were 4435.0298±149 and 4408.2150±1021 ng/mL, respectively. The mean area under the serum concentration curve (AUC)0-t were 38108.2614±8583.6535 and 38457.5791±8105.2529 ng/hr/mL The mean ratios (test: reference) for Cmax, AUC0-t, were 99.7% and 98.5%, respectively. There were no significant differences in pharmacokinetic parameters between groups. Overall, the 90% confidence interval for the intra-individual ratios of the log-transformed Cmax and AUC values of the two formulations were within the BE interval of 80-125%. Conclusion: The study has demonstrated the BE of milixim and reference formulation of cefixime.